Women’s Subalternity and Subjugation in Postcolonial Literature: A Feminist Analysis of the Novel “All My Rage” (Journal of Asian Development Studies, 2023)
This article entitled “Subalternity in All My Rage by Sabaa Tahir: A Postcolonial Feminist Analysis” raises the issue of women's subalternity, suppression, and marginalization. The research study aims to investigate women as subaltern objects that have been marginalized, double colonized and suppressed through physical and mental torture in social and political contexts in All My Rage (2022). It shows the power of patriarchy and its impacts on women's lives. It demonstrates the struggle of Noor, the female protagonist in the novel, who is suffering physical violence and marginalization but still chasing her dream. It shows the impacts of marginalization and subalternity on women's lives in the novel. The research article relies on the theoretical framework of Gayatri Spivak's "Can the Subalterns Speak" (1988) as Spivak has presented this theory that focuses on the suppression and marginalization of an inferior class in society who have no access to power control and specifically she has used the term subaltern for the oppressed and subjugated women in Indian society. It uses the qualitative method for the textual analysis of the novel under the Can the Subalterns Speak (1988) paradigm. This research study will be beneficial to give a voice to subaltern and marginalized women in society, and it will also depict a realistic image of a society that considers women as an object of victimization, marginalization, and inferiority. This research study focuses on the understanding of All My Rage (2022) from a postcolonial feminist perspective with the lens of Can the Subalterns Speak (1988) to fulfill the knowledge gap.